1992
DOI: 10.1108/02686909210008586
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Accounting in the Curriculum

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…Perubahan kurikulum dapat menjadi "jalan masuk" akuntansi forensik sebagai mata kuliah tersendiri di Jurusan Akuntansi Untad. Rezaee et al (1996) menemukan sejumlah perguruan tinggi telah menyelenggarakan mata kuliah fraud atau akuntansi forensik.…”
Section: Metodeunclassified
“…Perubahan kurikulum dapat menjadi "jalan masuk" akuntansi forensik sebagai mata kuliah tersendiri di Jurusan Akuntansi Untad. Rezaee et al (1996) menemukan sejumlah perguruan tinggi telah menyelenggarakan mata kuliah fraud atau akuntansi forensik.…”
Section: Metodeunclassified
“…Rezaee and Burtin (1997) found that forensic accountants prefer to have forensic accounting as a stand-alone course while academics prefer to integrate forensic accounting into existing accounting courses. Rezaee et al (1996) report some disagreements among practitioners and academics on the topical content of the forensic accounting curriculum. To date, the topical content of forensic accounting in the accounting curriculum is highly debated and remains a fruitful area for future research.…”
Section: Educationmentioning
confidence: 99%
“…They found evidence that fraudrelated topics were taught in internal auditing courses. Rezaee et al (1996) found that few universities offer a course in fraud or forensic accounting. Buckhoff and Schrader (2000) examined the extent of forensic accounting education in the US and found that US universities considered forensic accounting to be moderately important for inclusion in the accounting curriculum.…”
Section: Educationmentioning
confidence: 99%
“…This emphasizes the importance of this kind of education in the world. Rezaee, Lander, and Reinstein (1996) have identified four universities that teach forensic accounting and discussed the contents of the course in detail. Seda and Peterson Kramer (2015) mention that very little research on international forensic accounting education exists.…”
Section: Review Of Literaturementioning
confidence: 99%